Interaction between two timing microRNAs controls trichome distribution in Arabidopsis. - Xue-Yi Xue; Bo Zhao; Lu-Men Chao; Dian-Yang Chen; Wen-Rui Cui; Ying-Bo Mao; Ling-Jian Wang; Xiao-Ya Chen (PLoS Genetics, 2014)
The miR156-targeted squamosa promoter binding protein like (SPL) transcription factors function as an endogenous age cue in regulating plant phase transition and phase-dependent morphogenesis, but the control of SPL output remains poorly understood. In Arabidopsis thaliana the spatial pattern of trichome is a hallmark of phase transition and governed by SPLs. Here, by dissecting the regulatory network controlling trichome formation on stem, we show that the miR171-targeted lost meristems 1 (LOM1), LOM2 and LOM3, encoding GRAS family members previously known to maintain meristem cell polarity, are involved in regulating the SPL activity. Reduced LOM abundance by overexpression of miR171 led to decreased trichome density on stems and floral organs, and conversely, constitutive expression of the miR171-resistant LOM (rLOM) genes promoted trichome production, indicating that LOMs enhance trichome initiation at reproductive stage. Genetic analysis demonstrated LOMs shaping trichome distribution is dependent on SPLs, which positively regulate trichome repressor genes TRICHOMELESS 1 (TCL1) and TRIPTYCHON (TRY). Physical interaction between the N-terminus of LOMs and SPLs underpins the repression of SPL activity. Importantly, other growth and developmental events, such as flowering, are also modulated by LOM-SPL interaction, indicating a broad effect of the LOM-SPL interplay. Furthermore, we provide evidence that MIR171 gene expression is regulated by its targeted LOMs, forming a homeostatic feedback loop. Our data uncover an antagonistic interplay between the two timing miRNAs in controlling plant growth, phase transition and morphogenesis through direct interaction of their targets.